Tree turnover in a premontane neotropical forest (1998–2009) in Costa Rica - Estrada Chavarría, Armando (2011)
Tropical premontane forests between 700 and 1,400 m.a.s.l. represent a particular component of the gamma diversity of neotropical ecosystems; however, the extent of information about their dynamics lags behind the more studied lowland rain forests. Data from three 1-ha permanent plots in a premontane forest in Costa Rica collected during an 11-year period (1998–2009) suggested a high tree turnover rate for this ecosystem (high mortality rate, λ = 2.4% and annual recruitment, μ = 2.6%). The floristic composition did not significantly change during the study period, but its high dynamism (2.4%) exceeded that of several reported values from highly diverse neotropical lowland rain forests. The documented decrease in abundance (8.6%) and basal area (14.3%) of trees ≥10 cm in DBH differs from the general trend of increase described for several lowland tropical rain forests in recent decades. We detected a significant population reduction (>15% of individuals from 1998 to 2009) in several relatively abundant tree species, whereas the populations of the three most dominant species remained nearly constant. The high tree turnover recorded for this premontane forest might not have affected tree diversity; but it might be promoting recruitment and growth of some tree species that may eventually become over-dominant in this ecosystem.